2015
DOI: 10.1371/journal.pone.0127728
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Syphilis Point-of-Care Tests, from Pilot Study to National Programme Implementation in Zambia: A Qualitative Study of Healthcare Workers’ Perspectives on Testing, Training and Quality Assurance

Abstract: Syphilis affects 1.4 million pregnant women globally each year. Maternal syphilis causes congenital syphilis in over half of affected pregnancies, leading to early foetal loss, pregnancy complications, stillbirth and neonatal death. Syphilis is under-diagnosed in pregnant women. Point-of-care rapid syphilis tests (RST) allow for same-day treatment and address logistical barriers to testing encountered with standard Rapid Plasma Reagin testing. Recent literature emphasises successful introduction of new health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
89
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(91 citation statements)
references
References 50 publications
(67 reference statements)
2
89
0
Order By: Relevance
“…The main reasons for this are the lack of advocacy and political will to translate the evidence to national policy, lack of funding to make the tests affordable to those in need and the lack of a national control programmes to provide the architecture needed to coordinate all the different aspects of testing. Ensuring adequate training for health care workers and supplies of commodities were cited as key implementation barriers in Africa 30,31 .…”
Section: Malariamentioning
confidence: 99%
See 1 more Smart Citation
“…The main reasons for this are the lack of advocacy and political will to translate the evidence to national policy, lack of funding to make the tests affordable to those in need and the lack of a national control programmes to provide the architecture needed to coordinate all the different aspects of testing. Ensuring adequate training for health care workers and supplies of commodities were cited as key implementation barriers in Africa 30,31 .…”
Section: Malariamentioning
confidence: 99%
“…Countries need to harness the architecture provided by HIV PMTCT programmes to screen women for both infections using a single drop of blood in a single visit to a health care facility. Dual rapid HIV-syphilis RDTs with acceptable performance are now available 36 and the WHO, as well as many countries, has adopted these HIV and/or syphilis RDTs into their national guidelines 31,37 .…”
Section: Malariamentioning
confidence: 99%
“…An estimated 11 million people are infected with syphilis globally every year; of these 1.5 million are pregnant women [ 1 ]. Maternal syphilis can lead to adverse pregnancy outcomes (APO) in 53.4 - 81.8% cases [ 2 ] such as spontaneous abortions, intra-uterine growth retardation, still births, premature deliveries, low-birth weight, perinatal deaths and congenital disease among new-born babies [ 3 , 4 ]. To contribute towards control of maternal syphilis and its APOs, the World Health Organization (WHO) recommends antenatal screening of all pregnant women [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the impact of POC tests in screening pregnant women [49,50] have reported that there was a substantial increase in antenatal syphilis screening following introduction of these types of tests. This was true for different settings: from urban to rural, primary health care centres or hospitals, and in countries with different health systems and cultural and socioeconomic contexts in Africa, Asia, and South America.…”
Section: Impact Of Tests' Introductionmentioning
confidence: 99%
“…Health professionals and some authors also felt that training, supervision, and quality assurance must be strengthened and made an integrated part of POCT programmes [24,50,60,61]. Moreover, some health care workers stated that training would overcome their fear of communicating positive results and improve partners' notification [42].…”
Section: Impact Of Tests' Introductionmentioning
confidence: 99%